2016
DOI: 10.1097/01.epx.0000481358.12903.af
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pulmonary tuberculosis using Ziehl–Neelsen stain or cold staining techniques?

Abstract: Gabbett's stain was more accurate in the diagnosis of PTB compared with both ZN and MCS, even though the results were not statistically significant. It can replace ZN for initial diagnosis and follow up of cases. It is also easier, faster, and does not require a heating step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Comparison of ZN staining to the culture, which is regarded as gold standard, in this study showed higher sensitivity and slightly less specifi city than previous study (Abdelaziz et al 2016). The study conducted…”
Section: Discussionmentioning
confidence: 58%
“…Comparison of ZN staining to the culture, which is regarded as gold standard, in this study showed higher sensitivity and slightly less specifi city than previous study (Abdelaziz et al 2016). The study conducted…”
Section: Discussionmentioning
confidence: 58%
“…there is a significant relationship between smoking habit and the incidence of tuberculosis and people who smoke for a period of > 10 years have a 2 times greater risk of developing tuberculosis, through interviews conducted by respondents who have a smoking habit and suffer from tuberculosis claiming that they cannot stop smoking because they are addicted Even though they already know the dangers of smoking, the smoking behavior of people with tuberculosis has been going on for years and they still don't stop smoking even though they have tested positive for tuberculosis, smoking with the incidence of tuberculosis is a double problem because smoking helps spread the infection and worsens the severity of tuberculosis. [19]. [20].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to infectious etiologies identified by culture, microscopy identified seven patients with acid-fast bacilli (AFB) present in sputum smears. Because the presence of AFB in sputum is considered indicative of Mycobacterium tuberculosis infection, these patients were treated as tuberculosis (TB) patients [ 40 ]. Microscopy also identified Plasmodium species in three patients.…”
Section: Resultsmentioning
confidence: 99%